JAK2 V617F Analysis in Indonesian Myeloproliferative Neoplasms Patients - Fanti Saktini; Santosa Santosa; Sultana MH Faradz (Journal of Biomedicine and Translational Research, 2015)
Background : Three subtypes of myeloproliferative neoplasms (MPNs): Polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) showed overlapping phenotype. There has been no specific cytogenetic marker identified in these subtypes. JAK2 V617F mutation prevalence in Caucasian MPNs was first reported as 97% in PV, 57% in ET, and 50% in PMF.